The role of religious beliefs in ethics committee consultations for conflict over life-sustaining treatment. Issue 6 (30th January 2017) - Bandini, Julia I; Courtwright, Andrew; Zollfrank, Angelika A; Robinson, Ellen M; Cadge, Wendy
Abstract : Previous research has suggested that individuals who identify as being more religious request more aggressive medical treatment at end of life. These requests may generate disagreement over life-sustaining treatment (LST). Outside of anecdotal observation, however, the actual role of religion in conflict over LST has been underexplored. Because ethics committees are often consulted to help mediate these conflicts, the ethics consultation experience provides a unique context in which to investigate this question. The purpose of this paper was to examine the ways religion was present in cases involving conflict around LST. Using medical records from ethics consultation cases for conflict over LST in one large academic medical centre, we found that religion can be central to conflict over LST but was also present in two additional ways through (1) religious coping, including a belief in miracles and support from a higher power, and (2) chaplaincy visits. In-hospital mortality was not different between patients with religiously versus non-religiously centred conflict. In our retrospective cohort study, religion played a variety of roles and did not lead to increased treatment intensity or prolong time to death. Ethics consultants and healthcare professionals involved in these cases should be cognisant of the complex ways that religion can manifest in conflict over LST.